Short- and long-run goals in ultimatum bargaining: impatience predicts spite-based behavior - Espín, Antonio M.; Exadaktylos, Filippos; Herrmann, Benedikt; Brañas-Garza, Pablo (Frontiers in Behavioral Neuroscience, 2015)
The ultimatum game (UG) is widely used to study human bargaining behavior and fairness norms. In this game, two players have to agree on how to split a sum of money. The proposer makes an offer, which the responder can accept or reject. If the responder rejects, neither player gets anything. The prevailing view is that, beyond self-interest, the desire to equalize both players’ payoffs (i.e., fairness) is the crucial motivation in the UG. Based on this view, previous research suggests that fairness is a short-run oriented motive that conflicts with the long-run goal of self-interest. However, competitive spite, which reflects an antisocial (not norm-based) desire to minimize others’ payoffs, can also account for the behavior observed in the UG, and has been linked to short-run, present-oriented aspirations as well. In this paper, we explore the relationship between individuals’ intertemporal preferences and their behavior in a citywide dual-role UG experiment (N=713). We find that impatience (short-run orientation) predicts the rejection of low, “unfair” offers as responder and the proposal of low, “unfair” offers as proposer, which is consistent with spitefulness but inconsistent with fairness motivations. This behavior systematically reduces the payoffs of those who interact with impatient individuals. Thus, impatient individuals appear to be keen to minimize their partners’ share of the pie, even at the risk of destroying it. These findings indicate that competitively reducing other’s payoffs, rather than fairness (or self-interest), is the short-run goal in ultimatum bargaining.